Prevalence of Vitamin D Deficiency in Diabetic Neuropathy Patients in the South Indian Population - Mani, Vadivel; Kandregula, Madhavi; Venkatasan, Gayathri; N, Muninathan (Biomedical Sciences and Clinical Medicine, 2025)
Objective This research explores the prevalence of vitamin D deficiency among diabetic neuropathy patients in South India, highlighting the significant impact of this deficiency on health outcomes, particularly of the sensory-motor type. Methods A cross-sectional study at Koonaseema Institute of Medical Science and Research Foundation (KIMS&RF) found a significant association between vitamin D deficiency and diabetic neuropathy, with factors such as sociodemographic, risk factors, treatment duration, treatment modality, DPN score, hyperalgesia, and neuropathic pain. Results A study of 480 diabetic neuropathy patients found that 88.54% of them had a deficiency in vitamin D. Of those patients, 51.43% had insufficiency, while 37.11% had a more severe deficiency. The statistical analy-sis was conducted using Excel and the 16th edition of SPSS (Statistical Package for the Social Sciences). Literate individuals had lower vitamin D levels, while middle-class individuals were more likely. Obesity was linked to vitamin D insufficiency, with 65.60% of obese patients having insufficient vitamin D. Treatment modalities, sensory thresholds, and neuropathic pain symptoms were also associated with vitamin D deficiency. Conclusions This study in South India found that 88.54% of individuals, particularly those with diabetic neuropathy, were deficient in vitamin D. This is lower than in Egypt, but higher than in the UAE and China. Factors affecting vitamin D levels affect both males and females, with a higher impact on males. Complications from diabetic neuropathy are linked tovitamin D insufficiency. Further research is needed to validate these findings.